Association of Botulinum toxin treatment due to aesthetic corrections in the face with the level of happiness, anxiety and depression - Omar Suljagić; Emir Tupković; Kenana Ljuca; Faris Suljagić; Nadina Ljuca (Medicinski glasnik, 2025)
Aim: Any aesthetic procedure in the head and/or in the face might have an impact on psychological status of the treated participants. Aim: of this study was to investigate whether Botulinum toxin treatment for aesthetic purpose in the face influences on the level of happiness, depression and anxiety. Methods: This prospective cohort observational study included 30 participants, who were treated by botulinum toxin (Botox) due to aesthetic corrections. The treatment included laugh lines, frown lines and horizontal forehead lines. Preprocedural, three and six months after the treatment the participants were assessed by The Oxford Happiness Questionnaire (OHQ), The Beck Depression Inventory (BDI) and The Beck Anxiety Inventory (BAI) to determine the level of happiness, anxiety and depression was used. Results: Three months after the treatment by Botox the level of happiness was significantly increased (5.26±0.43 vs 4.3±0.34; p<0.0001). The levels of depression (7.6±6.0 vs 14.2±8.3; p<0.0001) and anxiety (8.8±6.3 vs 16.4±8.8; p<0.0001) were significantly decreased compared with preprocedural level. Significant increased level of happiness and decreased levels of depression and anxiety remained six months after the treatment, but attenuated. A dose of applied botulinum toxin was negatively correlated with the level of depression (r = -0.394; p=0.0421) and anxiety (r = -0.387; p=0.0302). Conclusion: Botulinum toxin treatment for aesthetic purpose in the face positively influences psychological status of the treated individual in the short-therm.
Keywords: Botox; Psychological factors; questionnaire